Asuhan Keperawatan Pada Anak Dengan Epilepsi - Rani Murtiani; IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
Epilepsy is a complex symptom of many brain dysfunction characterized by recurrent seizures due to excessive release of brain electrical charge and reversible motivation. Seizures are a result of uncontrolled electrical release from cerebral cortical nerve cells which are characterized by sudden attacks, mild disturbance of consciousness, motor activity, or sensory phenomenon disorders. Children with epilepsy will usually get impaired intelligence, language comprehension and impaired cognitive function. The impact of epilepsy on children will make a significant difference in IQ. In addition, epilepsy also has concomitant disease (developmental growth disorders) that will be suffered by the sufferer. This is what is known in the medical world as comorbidity and must be monitored by parents. The purpose of writing is that students are expected to be able to provide nursing care for children who have epilepsy. The result of this scientific paper is that students get an overview of nursing care in children with epilepsy. Emerging nursing problems in children with epilepsy include ineffective airway clearance, risk of injury, risk of fluid volume deficit, hypertermia, imbalance of nutrients less than body requirements, risk of infection, lack of family knowledge, and anxiety for children and parents.